Pengaruh Flashcard terhadap Hasil Belajar Materi Keragaman Tanaman Khas, Suku Bangsa, Tarian Indonesia di Sekolah Dasar - Mardani, Sinta Pramida; Halidjah, Siti; Kresnadi, Hery (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
The purpose of this study is to investigate the impact of flashcard learning media on student learning outcomes in grade III SDN 02 Sungai Raya on the topic of a variety of characteristic flora, ethnic groups, and regional dances of Indonesia. Experiments, quasi-experimental design study formats, and experimental designs with non-equivalent control groups were utilized. This study's population consists entirely of grade III SDN 02 Sungai Raya students. This study's sample consisted of class III A (28 students) as an experimental class and class III B (28 students) as a control class. The data gathered is in the form of student learning outcomes in both classrooms, provided directly by students. The approach used for data gathering is a measuring technique with data collecting instruments in the form of multiple-choice test questions. In addition, the t-test will be used to do the analysis. Based on the analytical findings, (tcount3,786) > (ttable1,674), implying that H0 is rejected. So there is a difference in the learning results of pupils taught using flashcard learning media and those taught without. This difference was subsequently examined using effect size, obtaining an ES of 0.90 with a high criterion. In grade III SDN 02 Sungai Raya, flashcard learning effects student learning results on the material of diversity of characteristic flora, ethnic groups, and regional dances of Indonesia.